The Authority of the Regent to cancel the Village Regulation on Village Revenue and Expenditure Budget based on Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management - Jaya, Hendro Kusuma; Muhibbin, Moh. (Ridwan Institute, 2024)
The research aims to investigate the Regent's authority to revoke Village Regulations on Village Revenue and Expenditure Budgets following Minister of Home Affairs Regulation Number 20 of 2018 on Village Financial Management. It employs normative legal research methods, utilizing statutory and conceptual approaches and analyzing primary, secondary, and tertiary legal sources qualitatively. The findings suggest that while Village Regulations lacking an evaluation mechanism, determined solely by the Village Head, contravene Article 69 paragraph (4) of Law Number 6 of 2014 on Villages, the Regent/Mayor cannot annul such regulations under Article 36 paragraph (1) of Minister of Home Affairs Regulation Number 20 of 2018 unless the Village Head disregards the Regent/Mayor's evaluation findings, maintaining the validity of the Village Regulation. The Regent's authority to annul Village Regulations ignoring Regent's evaluations, as per Minister of Home Affairs Regulation Number 20 of 2018, conflicts with Article 24A paragraph (1) of the 1945 Constitution of the Republic of Indonesia.